Defining and Adopting Clinical Performance Measures in Graduate Medical Education: Where Are We Now and Where Are We Going?. (May 2019) - Smirnova, Alina; Sebok-Syer, Stefanie S.; Chahine, Saad; Kalet, Adina L.; Tamblyn, Robyn; Lombarts, Kiki M.J.M.H.; van der Vleuten, Cees P.M.; Schumacher, Daniel J.
Abstract : Assessment and evaluation of trainees' clinical performance measures is needed to ensure safe, high-quality patient care. These measures also aid in the development of reflective, high-performing clinicians and hold graduate medical education (GME) accountable to the public. Although clinical performance measures hold great potential, challenges of defining, extracting, and measuring clinical performance in this way hinder their use for educational and quality improvement purposes. This article provides a way forward by identifying and articulating how clinical performance measures can be used to enhance GME by linking educational objectives with relevant clinical outcomes. The authors explore four key challenges: defining as well as measuring clinical performance measures, using electronic health record and clinical registry data to capture clinical performance, and bridging silos of medical education and health care quality improvement. The authors also propose solutions to showcase the value of clinical performance measures and conclude with a research and implementation agenda. Developing a common taxonomy of uniform specialty-specific clinical performance measures, linking these measures to large-scale GME databases, and applying both quantitative and qualitative methods to create a rich understanding of how GME affects quality of care and patient outcomes is important, the authors argue. The focus of this article is primarily GME, yet similar challenges and solutions will be applicable to other areas of medical and health professions education as well.